PENGARUH MODAL SOSIAL TERHADAP PRODUKTIVITAS PETANI (STUDI KASUS DI KECAMATAN SERBAJADI KABUPATEN SERDANG BEDAGAI) - Raha yu; M. Sahnan (Universitas Islam Sumatera Utara, 2020)
Social welfare relates to social conditions, where social issues can be addressed satisfactorily, social needs can be fulfilled well, having a sense of security in life and freely open social opportunities. Social capital that exists in the community can enrich the community and can even minimize the chances of conflict. The type of contribution of the agricultural sector in Serdang District Bedagai is the largest produced by the commodity of food crops (BPS, 2014). Decision of farmers to grow crops because it is based on the needs of eating farmers ' families as well as the price of food ingredients are increasingly expensive. The high value of social capital that is owned by a region can help farmers in terms of production, distribution and innovation. Based on the explanation, researchers are interested in researching how big the social capital is on farmers in the district of Serba Jadi, then its influence on the productivity of existing farmers in the sub-district of Serdang Bedagai District. The role of capital can help increase agricultural productivity, but not many people acknowledge that the increase of human capital and social capital can raise the productivity of farmers, while the productivity of farmers in District Department of district Serdang Bedagai is low. This research aims to determine the influence of social capital both partially and simultaneously to the productivity of farmers in the subdistrict of Serdang Bedagai district.This research uses a quantitative approach. Data collection techniques use questionnaires and documentation, while data analysis techniques use double regression analysis. The results showed that: (1) Variable Trust has no positive effect on farmer productivity (2) Participation variables have no positive effect on farmer productivity (3) network variables have no positive effect To farmer productivity (4) variable social norms positively and significantly influence on farmers ' productivity (5) Variable trust, participation, networking, and social norms positively influence together towards productivity Farmers.